Analyses of MMP20 Missense Mutations in Two Families with Hypomaturation Amelogenesis Imperfecta - Kim, Youn Jung; Kang, Jenny; Seymen, Figen; Koruyucu, Mine; Gencay, Koray; Shin, Teo Jeon; Hyun, Hong-Keun; Lee, Zang Hee; Hu, Jan C.-C.; Simmer, James P.; Kim, Jung-Wook (Frontiers in Physiology, 2017)
Amelogenesis imperfecta is a group of rare inherited disorders that affect tooth enamel formation, quantitatively and/or qualitatively. The aim of this study was to identify the genetic etiologies of two families presented with hypomaturation amelogenesis imperfecta. DNA was isolated from peripheral blood samples of participating family members. Whole exome sequencing was performed using DNA samples from the two probands. Sequencing data was aligned to the NCBI human reference genome (NCBI build 37.2, hg19) and sequence variations were annotated with the dbSNP build 138. Mutations in MMP20 gene were identified in both probands. A homozygous missense mutation (c.678T>A; p.His226Gln) was identified in the consanguineous Family 1. Compound heterozygous MMP20 mutations (c.540T>A, p.Tyr180* and c.389C>T, p.Thr130Ile) were identified in the non-consanguineous Family 2. Affected persons in the family 1 showed hypomaturation AI with dark brown discoloration, which is similar to the clinical phenotype in a previous report with the same mutation. However, the dentition of the proband in the family 2 exhibited slight yellowish discoloration with reduced transparency. The functional analysis showed that the p.Thr130Ile mutant protein had reduced activity of MMP20, while there’s no functional MMP20 in the proband of family 1. These results expand the mutational spectrum of the MMP20 and broaden our understanding of genotype-phenotype correlations in amelogenesis imperfecta.